Japanese encephalitis virus perturbs PML-nuclear bodies by engaging in interactions with distinct porcine PML isoforms - Yang, Songbai; Liu, Huaijin; Chen, Zhenyu; Wang, Han; Li, Xiangchen; Zhou, Xiaolong; Zhao, Ayong (Frontiers in Cellular and Infection Microbiology, 2023)
Abstract： Promyelocytic leukemia (PML) protein constitutes an indispensable element within PML-nuclear bodies (PML-NBs), playing a pivotal role in the regulation of multiple cellular functions while coordinating the innate immune response against viral invasions. Simultaneously, numerous viruses elude immune detection by targeting PML-NBs. Japanese encephalitis virus (JEV) is a flavivirus that causes Japanese encephalitis, a severe neurological disease that affects humans and animals. However, the mechanism through which JEV evades immunity via PML-NBs has been scarcely investigated. In the present study, PK15 cells were infected with JEV, and the quantity of intracellular PML-NBs was enumerated. The immunofluorescence results indicated that the number of PML-NBs was significantly reduced in JEV antigen-positive cells compared to viral antigen-negative cells. Subsequently, ten JEV proteins were cloned and transfected into PK15 cells. The results revealed that JEV non-structural proteins, NS2B, NS3, NS4A, NS4B, and NS5, significantly diminished the quantity of PML-NBs. Co-transfection was performed with the five JEV proteins and various porcine PML isoforms. The results demonstrated that NS2B colocalized with PML4 and PML5, NS4A colocalized with PML1 and PML4, NS4B colocalized with PML1, PML3, PML4, and PML5, while NS3 and NS5 interacted with all five PML isoforms. Furthermore, ectopic expression of PML isoforms confirmed that PML1, PML3, PML4, and PML5 inhibited JEV replication. These findings suggest that JEV disrupts the structure of PML-NBs through interaction with PML isoforms, potentially leading to the attenuation of the host's antiviral immune response.